Dificuldade no domínio de fonemas do português por crianças bilíngües de português e pomerano - Benincá, Ludimilla Rupf (2008)
Despite the fact that Brazil has Portuguese as its only official language it is still a multilingual country. Throughout the country there are speakers who acquire languages other than Portuguese in the home and learn the official language as if it were a foreign language, often only when they start school. This is what happens with the Pomeranian descendents who speak Pomeranian – an immigration language of the now extinct Pomerania – still widely used by the remaining groups of descendants of those immigrants who originally brought the language to Brazil This language is normally learned in the context of the home, and is used socially within the community, during religious rituals, in the domestic environment and when farming. The Portuguese spoken by these children is full of the characteristics of their mother tongue, which often causes prejudice and can interfere with the learning of Portuguese. Therefore, this work describes the Portuguese spoken by these descendants and identifies the characteristics which interfere with the learning of Portuguese, as well as the typical misspellings produced by this population. The objective is to create a reference work which can be used as a basis for subsequent educational proposals that consider the peculiarities of the group. For this, two corpora of analysis were used: oral data, obtained through recorded interviews, and written data, consisting of written texts produced by informants, both collected from fifth grade students of elementary schools in the community of Alto Rio Possmoser, Santa Maria de Jetibá, in the state of Espírito Santo. Among the occurrences found in the oral corpus, one important finding is related to the variation in syllable structure, which occurs mainly through the phenomenon of unblocking, caused by the erasure of the tap in coda position, a phenomenon which is also frequent in monolingual speakers. Problematic changes of the syllabic pattern itself were also identified. One very common process, which does not occur systematically in monolingual speakers and which can therefore be considered a specific characteristic of the speakers in question, was a distortion of the voicing value, whereby voiced consonants are substituted by the corresponding unvoiced ones. This characteristic was also present in the written texts. The most common errors in the written data involved syllabic structuring and the exchange of phonemes, characterized by the graphic representation of a different phoneme from that which formed the word in question. These exchanges were mainly generated by the oral influence of consonant voicing, and the difficulty in controlling the different phonemes represented by each letter. These problems demonstrate the necessity for education based on specific needs.